Visual Temporal Acuity Is Related to Auditory Speech Perception Abilities in Cochlear Implant Users. Issue 2 (March 2017) - Jahn, Kelly N.; Stevenson, Ryan A.; Wallace, Mark T.
Abstract : Objectives: Despite significant improvements in speech perception abilities following cochlear implantation, many prelingually deafened cochlear implant (CI) recipients continue to rely heavily on visual information to develop speech and language. Increased reliance on visual cues for understanding spoken language could lead to the development of unique audiovisual integration and visual-only processing abilities in these individuals. Brain imaging studies have demonstrated that good CI performers, as indexed by auditory-only speech perception abilities, have different patterns of visual cortex activation in response to visual and auditory stimuli as compared with poor CI performers. However, no studies have examined whether speech perception performance is related to any type of visual processing abilities following cochlear implantation. The purpose of the present study was to provide a preliminary examination of the relationship between clinical, auditory-only speech perception tests, and visual temporal acuity in prelingually deafened adult CI users. It was hypothesized that prelingually deafened CI users, who exhibit better (i.e., more acute) visual temporal processing abilities would demonstrate better auditory-only speech perception performance than those with poorer visual temporal acuity. Design: Ten prelingually deafened adult CI users were recruited for this study. Participants completed a visual temporal order judgment task to quantify visual temporal acuity. To assess auditory-only speech perception abilities, participants completed the consonant–nucleus–consonant word recognition test and the AzBio sentence recognition test. Results were analyzed using two-tailed partial Pearson correlations, Spearman's rho correlations, and independent samples t tests. Results: Visual temporal acuity was significantly correlated with auditory-only word and sentence recognition abilities. In addition, proficient CI users, as assessed via auditory-only speech perception performance, demonstrated significantly better visual temporal acuity than nonproficient CI users. Conclusions: These findings provide the first behavioral evidence that visual temporal acuity is related to post implantation CI proficiency as indexed by auditory-only speech perception performance. These preliminary data bring to light the possible future role of visual temporal acuity in predicting CI outcomes before implantation, as well as the possible utility of visual training methods in improving CI outcomes.